Global Inequality in National Food Supplies and Diet-related Health Outcomes, 1970–2010 (P04-094-19). (13th June 2019) - Bell, Winnie; Lividini, Keith; Masters, William
Abstract: Objectives: The global food system has changed rapidly over recent decades, with large shifts in agricultural supply conditions, international trade, food manufacturing and nutrient availability. These shifts have contributed to both positive and negative impacts on health and wellbeing with some countries catching up while others have fallen further below international norms. We aim to quantify long-run changes in the food supply and diet-related health disparities across countries, to illustrate how inequality has changed from the 1970 s to the 2010 s. Methods: Data were drawn from publicly available sources, using food supply from the United Nations Food and Agriculture Organization (FAO) and diet-related health outcomes from the NCD Risk Factor Collaboration (NCD-RisC) and the Joint Monitoring Programming, a collaboration of the World Bank, the World Health Organization, and UNICEF. We used techniques from economics (Lorenz curves, Gini coefficients, and Pen's Parade) to generate novel visualizations and metrics for global inequality and disparities in national food supply and diet-related health outcomes across countries. Results: We computed global inequality in food supplies as available dietary energy from all fruits and vegetables, all animal source foods, and all foods other than starchy staples, and inequality in diet-related outcomes such as overweight and obesity, underweight, stunting, raised blood pressure, and diabetes. Results showed greater equality in food supplies and diet-related health outcomes converging at higher prevalence levels, while stunting and underweight became more unequal and more highly concentrated in a few high-burden countries. For example, the Gini coefficient for energy from fruit and vegetables (0.36 to 0.27), energy from animal source foods (0.51 to 0.33), and overweight and obesity (0.39 to 0.27) decreased indicating greater equality, while the Gini coefficient for underweight increased (0.40 to 0.47) demonstrating greater disparity. Conclusions: Convergence in availability of harmful dietary components and negative health outcomes occurred faster than convergence in beneficial nutrients and positive outcomes. This research can help to inform the design of policies and programs aimed at achieving the UN Sustainable Development Goals and other targets for global food systems. Funding Sources: Wellcome Trust.